(untitled) (Research, Society and Development, 2024)
Objective: The objective of this article was to address children with ASD and the impact that clothing used by dentists can have. Methodology: Searches were carried out through data available on PUBMED Central and BVS/BIREME, with research carried out on the Scielo platforms, CAPES Newspaper Portal, Web of Science, The Cochrane Library, Science Direct, Newspapers, Chinese Literature and the Google Scholar platform. We obtained 44 articles addressing various information such as: the impact of recreational clothing on the interaction of children with TEA with dentistry. This literature review article was created from readings of Mattos’s (2015) study. Results: From this study, it is confirmed that children with TEA tend to be hypersensitive to cores and luminosities, requiring most of the time dental treatment, using playful clothing, an essential tool to develop receptivity during consultations, in addition to creating a better patient x professional relationship.